2008
DOI: 10.1016/j.jalz.2008.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Unobtrusive assessment of activity patterns associated with mild cognitive impairment

Abstract: Background Timely detection of early cognitive impairment is difficult. Measures taken in the clinic reflect a single snapshot of performance that may be confounded by the increased variability typical in aging and disease. We evaluated the use of continuous, long-term and unobtrusive in-home monitoring to assess neurological function in healthy and cognitively impaired elders. Methods Fourteen older adults 65 years and older living independently in the community were monitored in their homes using an unobtr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
145
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 167 publications
(149 citation statements)
references
References 40 publications
4
145
0
Order By: Relevance
“…Clinicians attempt to accurately describe the health state of a patient via gait analysis in order to diagnose a gait disorder or to decide on a treatment that may improve patients’ gait [4, 5]. When dealing with elderly patients, the assessment of balance while standing and walking has proved to be a predictor of falls [6] and is related to self-rated health status [7], cognitive impairment caused by dementia [8, 9], mortality and morbidity [10, 11]. …”
Section: Introductionmentioning
confidence: 99%
“…Clinicians attempt to accurately describe the health state of a patient via gait analysis in order to diagnose a gait disorder or to decide on a treatment that may improve patients’ gait [4, 5]. When dealing with elderly patients, the assessment of balance while standing and walking has proved to be a predictor of falls [6] and is related to self-rated health status [7], cognitive impairment caused by dementia [8, 9], mortality and morbidity [10, 11]. …”
Section: Introductionmentioning
confidence: 99%
“…However, recent studies have shown that early changes in motor capabilities precede and may be indicative of a cognitive impairment [4], and that subjects with mild cognitive impairment exhibit a more variable and less consistent pattern of activity throughout the day [5]. Accordingly, and with the advancement in technology and the proliferation of smart systems, a good alternative to the traditional clinical paradigm is to bring assessment into the daily activity of a person in their home environment via unobtrusive sensors and smart systems.…”
Section: Introductionmentioning
confidence: 99%
“…The authors find that, while longitudinal measurements are insightful, more fine-grained activity detection would be helpful (Petersen et al, 2015). In another study, Hayes et al (2008) recorded and • Parkinson, dementia and sleep disorders Respiration rate…”
Section: Wearable Sensors Have a Great Potential To Monitor Health Stmentioning
confidence: 99%